Space efficient meta-grid lines for mutual coupling reduction in two-port planar monopole and DRA array - Mishra, Mohit (2023)
Traditionally used mutual coupling (MC) reduction techniques such as electromagnetic bandgap structures, isolators and neutralization lines require extra space between radiators. Besides, metamaterial-based techniques require multi-layer arrangements. However, the proposed meta-grid lines overcomes the above demerits by integrating meta-grid lines in the ground plane itself. As a proof-of-concept, two-port CPW-fed monopole antenna array (TPCFMAA) and two-port DRA array (TPDRAA) are designed, fabricated and tested. It has been observed that the TPCFMAA has mutual coupling below -20 dB for frequency between 2.6 to 4.4 GHz. The envelope correlation coefficient reduces from 0.072 to 0.026 by integrating meta-grid lines in the ground plane of the TPCFMAA. At 3.5 GHz, the inter-element distance between the antennas is noted to be 0.015λh (λh= highest operating wavelength). The TPDRAA's operating frequency can be tuned by changing the parameters of the annular ring slot in the excitation patch. The bandwidth of TPDRAA can be further increased by merging the two resonances of the two annular ring slots in the excitation patch. For TPDRAA, the measured -10 dB impedance bandwidth is from 5.65 to 6.55 GHz. The mutual coupling between the antenna elements is seen to be below -16 dB for an inter-element spacing of 4.8 mm, which is 0.090λh. The measured gain of TPDRAA within the bandwidth is from 4.17 dBi to 5.2 dBi. The TPCFMAA can be used in 3.5 GHz Internet of Vehicles (IoV) multi-user MIMO service, whereas the TPDRAA can be used for satellite communication in the 5.925 to 6.425 GHz frequency band, WiMAX in the 5.7 to 5.85 GHz band, ISM in the 5.725 to 5.85 GHz band, and WLAN in the 5.8 GHz band.